2003
DOI: 10.1001/archneur.60.11.1566
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Neuroradiological Features of Patients With Spinocerebellar Ataxias From Korean Kindreds

Abstract: The clinical and neuroradiological characteristics of Korean patients with SCAs might be helpful in detecting underlying gene mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Our gene analysis data showed that the number of CAG repeats in SCA2 coding region of the proband was 44 times, her mother was 36 times, and her brother was 38 times. All CAG repeats were found within the abnormal range, and this observation was consistent with the findings of a previous study [14]. The above-referred changes were found to have a negative correlation with age at which the disease onset occurred.…”
Section: Discussionsupporting
confidence: 92%
“…Our gene analysis data showed that the number of CAG repeats in SCA2 coding region of the proband was 44 times, her mother was 36 times, and her brother was 38 times. All CAG repeats were found within the abnormal range, and this observation was consistent with the findings of a previous study [14]. The above-referred changes were found to have a negative correlation with age at which the disease onset occurred.…”
Section: Discussionsupporting
confidence: 92%
“…Given the diversity of dystonias, it would be surprising if both cases are not rampant. Nonetheless there are clear examples of dystonia in patients that appear to be causally related to cerebellar dysfunction, particularly when dystonia manifests as a symptom in cerebellar-centric disorders such as spinocerebellar or episodic ataxias (Bang et al, 2003; Kawarai et al, 2016; Mariotti et al, 2007; Muglan et al, 2016; Nakagaki et al, 2002; Sethi and Jankovic, 2002). In some cases, lesioning or stimulation of the cerebellum has been documented to improve the symptoms, corroborating the notion that in some patients, dystonia can arise from cerebellar dysfunction (Koch et al, 2014; Panov et al, 2013; Teixeira et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic Resonance Imaging (MRI) of SCA7 patients typically reveals marked atrophy of the cerebellum and pons (Figure 1b), while a subset of patients may also demonstrate high T2 signal intensity in transverse pontine fibers (16). MRIbased volumetric analysis demonstrated that SCA7 patients have significantly more pontine atrophy than patients with other SCAs.…”
Section: Genetic Features Of Sca7mentioning
confidence: 99%